(untitled) (Global Scientific Review, 2022)
This article presents effective ways to motivate students, technologies for using these methods. The article also provides comprehensive information on why incentives are needed. Taking a lesson in a situation using these effective methods will help to educate the next generation in the spirit of healthy competition